The Role of Job Stress as Mediator on the Relationship Between Job Demands on PT X Outsourced Driver Turnover Intention - Paramarta, Nata Adyana; Setiyowati, Ninik (Universitas Negeri Malang, 2024)
Turnover intention is a detrimental occurrence that frequently arises in many enterprises. Elevated levels of turnover intention can detrimentally affect the firm. Job demands and job stress are influential elements that contribute to increased turnover intention. This research aimed to examine the impact of job demands on turnover intention while considering the mediating role of job stress variables. A correlational quantitative methodology was employed, with 74 respondents who completed a questionnaire. Reliability was evaluated using Cronbach’s alpha technique with job demands with a Cronbach’s alpha value of 0.698, job stress with a Cronbach’s alpha value of 0.539, and turnover intention with a Cronbach’s alpha value of 0.855. A mediator analysis was conducted using the JASP software to assess the importance of the three variables. The analysis results indicate that job demands statistically impact turnover intention (p-value equals .005), job demands substantially affect job stress (p-value equals .001), and job stress significantly affects turnover intention (p-value equals .015). This research demonstrates that job stress plays a mediating function in the connection between job demands and turnover intention, and this association is statistically significant with a p-value of .035. These findings suggest that job stress significantly motivates people with high job demands to consider leaving their current employment.